(untitled) (Bangladesh Journal of Child Health, 2018)
Background: Lead toxicity is one of the most frequently reported unintentional toxic heavy metal exposures and the leading cause of single metal toxicity in children. Lead has no known beneficial function in human metabolism, rather its exposure has various detrimental effect on child health. Lead exposure causes activation of several cellular and molecular processer in leukemic cells so the purpose of the study was to measure serum concentration of lead in newly diagnosed acute lymphoblastic leukemia (ALL) patients. Methodology: The study group consisted of newly diagnosed ALL patients ranging from 2 to 12 years who were admitted at the Department of Pediatrics in Dhaka Medical College Hospital (DMCH), from February 2013 to January 2014 and age and sex matched healthy children’s were selected as controls. Serum measurements for lead were performed by Atomic absorption spectrophotometer in Analytical Chemistry Laboratory of Atomic Energy Centre Ramna, Dhaka. Results: The ALL group composed of 30 patients and 33 healthy children in the control group. There was no significant difference in the age (p=0.781) and sex (p=0.572) of the two groups. The mean serum lead level of ALL patient group (234.8±162.9 μg/L) was significantly higher than that of the control group (23.6±12.6 μg/L). There was significant difference of serum lead level in children with ALL and control group (p<0.05). Conclusion: Serum lead (PB) level was significantly raised in acute lymphoblastic leukemia patients. Bangladesh J Child Health 2018; VOL 42 (1) :26-29